Silicon carbide ceramics and preparation method thereof

By covering the polymer resin layer on the surface of nano silicon carbide and adding sintering aids, the problem of agglomeration of nano silicon carbide ceramics during sintering is solved, and the high thermal conductivity and excellent mechanical properties of silicon carbide ceramics are achieved.

CN118164763BActive Publication Date: 2024-12-24SUZHOU KAIXIN SEMICON TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410076260.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-18
Publication Date
2024-12-24
Estimated Expiration
2044-01-18

AI Technical Summary

Technical Problem

Nano-silicon carbide ceramics are prone to agglomeration during the sintering process, resulting in uneven distribution of silicon carbide powder in the molded blank, forming large irregular holes or cracks, reducing their mechanical properties and thermal conductivity.

Method used

By grafting the polymer resin layer on the surface of nano silicon carbide, it prevents agglomeration and forms a carbon black layer during degreasing and sintering, reducing the oxygen vacancies concentration, and using α-silicon carbide and sintering aids to achieve the ceramic grains. Rapid densification.

Benefits of technology

It improves the uniformity, density and thermal conductivity of silicon carbide ceramics, and enhances its mechanical properties and thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118164763B_ABST
    Figure CN118164763B_ABST
Patent Text Reader

Abstract

The present invention relates to a silicon carbide ceramic and a preparation method thereof. The raw materials for its preparation include modified nano silicon carbide, a sintering aid and carbon powder; the modified nano silicon carbide includes nano α-silicon carbide and a polymer resin layer, and the polymer resin layer is coated on the surface of the nano α-silicon carbide. The above silicon carbide ceramic can prevent the agglomeration of nano silicon carbide by grafting and coating the polymer resin layer on the surface of nano silicon carbide, thereby improving the sintering uniformity of the ceramic embryo; at the same time, the polymer resin layer coated on the surface of nano silicon carbide is in-situ carbonized during the degreasing and sintering process to form a carbon black layer, which promotes the sintering of ultrafine grain silicon carbide ceramics, improves the uniformity of the grain structure and the thermal conductivity of the silicon carbide ceramics; the selection of α-silicon carbide in coordination with the sintering aid and carbon black can achieve rapid densification of ceramic grains, prevent abnormal growth of grains, further improve the density and uniformity of silicon carbide ceramic grains, and thus improve the mechanical properties and thermal conductivity of silicon carbide ceramics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a silicon carbide ceramic and a preparation method thereof. Background Art

[0002] Silicon carbide ceramics have the advantages of low density, high thermal conductivity, low thermal expansion coefficient, high wear resistance, high strength, and high hardness, making them widely used in fields such as ceramics for functional electronic devices, advanced refractory structural materials, wear-resistant and heat-resistant ceramic ball valves and sealing components, abrasives, etc.

[0003] Ultrafine-grained silicon carbide ceramics have higher density and higher thermal conductivity than ordinary ceramics. The powder used in ultrafine-grained silicon carbide ceramics can be nano-silicon carbide ceramic powder. Nano-silicon carbide ceramic powder is the preferred material for preparing ultrafine-grained silicon carbide ceramics due to its high sintering activity. However, nano-silicon carbide powder is prone to agglomeration. Powder agglomeration will lead to uneven distribution of silicon carbide powder in the molded body, resulting in "differential sintering" due to different incorporation rates of various parts during the sintering process, thereby forming large irregular holes or crack-like holes in the sintered body. These holes become potential crack sources, which greatly reduce the mechanical properties of silicon carbide ceramics, and also reduce the density and thermal conductivity of silicon carbide ceramics. Summary of the invention

[0004] Based on this, it is necessary to provide a silicon carbide ceramic with high thermal conductivity and good mechanical properties and a preparation method thereof.

[0005] The first aspect of the present invention provides a silicon carbide ceramic, the preparation raw materials of which include modified nano silicon carbide, a sintering aid and carbon powder; the modified nano silicon carbide includes nano α-silicon carbide and a polymer resin layer, and the polymer resin layer is coated on the surface of the nano α-silicon carbide.

[0006] The above-mentioned silicon carbide ceramics can prevent the agglomeration of nano-silicon carbide by grafting and coating the polymer resin layer on the surface of nano-silicon carbide, improve the uniformity of nano-silicon carbide in the ceramic body, and improve the sintering uniformity of the ceramic body; at the same time, the polymer resin layer coated on the surface of nano-silicon carbide is carbonized in situ during the degreasing and sintering process to form a carbon black layer, and these carbon black layers can react with silicon oxide on the surface of the nano-powder to reduce the oxygen vacancy concentration in the silicon carbide grains, promote the sintering of ultrafine-grained silicon carbide ceramics, and improve the uniformity of the grain structure and the thermal conductivity of the silicon carbide ceramics; further, selecting α-silicon carbide as the nano-silicon carbide raw material and adding sintering aids and carbon black can achieve rapid densification of ceramic grains, prevent abnormal grain growth, further improve the density and uniformity of silicon carbide ceramic grains, and thereby improve the mechanical properties and thermal conductivity of silicon carbide ceramics.

[0007] In some embodiments, the raw materials include 90 to 98 parts of modified nano silicon carbide, 0.5 to 7.0 parts of sintering aid and 0.5 to 3.0 parts of carbon powder, by weight.

[0008] In some embodiments, the silicon carbide ceramic satisfies at least one of the following conditions:

[0009] (1) In the modified nano-silicon carbide, the thickness of the polymer resin layer is 5nm~10nm;

[0010] (2) The average particle size of the nano-α-silicon carbide is 20nm~200nm;

[0011] (3) The mass of the polymer resin layer accounts for 2wt% to 5wt% of the mass of the nano-α-silicon carbide.

[0012] In some embodiments, the silicon carbide ceramic satisfies at least one of the following conditions:

[0013] (1) The material of the polymer resin layer is epoxy resin;

[0014] (2) The sintering aid is at least one selected from alumina, yttrium oxide, magnesium oxide, boron, boron carbide, boron phosphide, boron nitride, aluminum nitride and aluminum;

[0015] (3) The average particle size of the sintering aid is 50nm~500nm;

[0016] (4) The average particle size of the carbon powder is 20nm~200nm.

[0017] In some embodiments, the nano-α-silicon carbide is surface hydroxylated nano-α-silicon carbide; and / or,

[0018] The modified nano-silicon carbide further comprises a non-ionic surfactant, and the non-ionic surfactant is connected to the surface of the polymer resin layer.

[0019] In some embodiments, the nonionic surfactant is selected from at least one of dipropylene triamine and coconut fatty acid diethylamide.

[0020] In some embodiments, the raw material for preparation further includes 1 to 3 parts of a binder by weight.

[0021] A second aspect of the present invention provides a method for preparing the above silicon carbide ceramic, the method comprising the following steps:

[0022] The prepared raw materials are mixed and then molded to obtain a ceramic body;

[0023] The ceramic body is subjected to degreasing treatment and sintering treatment in sequence.

[0024] In some embodiments, the degreasing treatment is performed at a temperature of 350°C to 500°C for a time of 1 hour to 3 hours; and / or the sintering treatment is performed at a temperature of 1850°C to 2150°C for a holding time of 2 hours to 4 hours.

[0025] In some embodiments, the preparation method further includes a preparation step of modified nano-silicon carbide, including:

[0026] The nano-α-silicon carbide is subjected to hydroxylation treatment to obtain surface hydroxylated nano-α-silicon carbide;

[0027] The surface of the hydroxylated nano-α-silicon carbide is coated with a polymer resin to obtain the nano-α-silicon carbide with a polymer resin layer coated on the surface.

[0028] In some embodiments, the preparation step of the modified nano-silicon carbide further includes:

[0029] The step of connecting a nonionic surfactant to the surface of the nano-α-silicon carbide coated with a polymer resin layer.

[0030] In some embodiments, the preparation method further comprises a granulation step before the forming step, and obtains a composite powder with an average particle size of 50 μm to 200 μm.

[0031] In some embodiments, the forming is performed by cold pressing, and the forming pressure is 50 MPa to 300 MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are merely embodiments of the present application, and ordinary technicians in this field can obtain other drawings based on the disclosed drawings without paying any creative work.

[0033] Figure 1 This is a microscopic morphology of the nano-silicon carbide powder modified with hydantoin resin in Example 1.

[0034] Figure 2 This is the SEM image of the ultrafine silicon carbide ceramic in Example 1.

[0035] Figure 3 This is the SEM image of the coarse-grained silicon carbide ceramic in Comparative Example 1.

[0036] Description of reference numerals:

[0037] 1. Nano-α-silicon carbide;

[0038] 2. Hydantoin epoxy resin. DETAILED DESCRIPTION

[0039] In order to facilitate the understanding of the present invention, the present invention is described more comprehensively below, and preferred embodiments of the present invention are provided. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. It should be understood that the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0041] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0042] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0043] Nano silicon carbide ceramic powder has high sintering activity and is the preferred material for preparing ultrafine grain silicon carbide ceramics. However, nano silicon carbide powder has high surface activity, and the silicon dioxide film on the surface of the powder is very easy to bond with water vapor in the atmosphere to form hydroxyl groups (-OH), and accelerate the process of physical adsorption of moisture by the powder (through hydrogen bonds), resulting in soft agglomeration of the nano powder. The inventor found that the agglomerated nano powder is difficult to restore through vacuum drying, which can only remove the moisture physically adsorbed on the surface of the powder, and the agglomerated powder bonded by hydrogen bonds on the surface further reacts chemically during heating to form "oxygen bridges" and produce hard agglomerates. Powder agglomeration will lead to unevenness of the formed body, which will lead to "differential sintering" due to different incorporation rates of various parts during the sintering process, thereby forming large irregular holes or crack-like holes in the sintered body.

[0044] In one embodiment of the present invention, a silicon carbide ceramic is provided, wherein the raw materials for preparing the silicon carbide ceramic include modified nano silicon carbide, a sintering aid and carbon powder; the modified nano silicon carbide includes nano α-silicon carbide and a polymer resin layer, and the polymer resin layer is coated on the surface of the nano α-silicon carbide.

[0045] The above-mentioned silicon carbide ceramics can prevent the agglomeration of nano-silicon carbide by grafting and coating the polymer resin layer on the surface of nano-silicon carbide, improve the uniformity of nano-silicon carbide in the ceramic body, and improve the sintering uniformity of the ceramic body; at the same time, the polymer resin layer coated on the surface of nano-silicon carbide is carbonized in situ during the degreasing and sintering process to form a carbon black layer, and these carbon black layers can react with silicon oxide on the surface of the nano-powder to reduce the oxygen vacancy concentration in the silicon carbide grains, promote the sintering of ultrafine-grained silicon carbide ceramics, and improve the uniformity of the grain structure and the thermal conductivity of the silicon carbide ceramics; further, selecting α-silicon carbide as the nano-silicon carbide raw material and adding sintering aids and carbon black can achieve rapid densification of ceramic grains, prevent abnormal grain growth, further improve the density and uniformity of silicon carbide ceramic grains, and thereby improve the mechanical properties and thermal conductivity of silicon carbide ceramics.

[0046] In some embodiments, the raw materials include 90 to 98 parts of modified nano silicon carbide, 0.5 to 7.0 parts of sintering aid and 0.5 to 3.0 parts of carbon powder, by weight.

[0047] The above-mentioned "90 to 98 parts of modified nano-silicon carbide" can be understood as the number of modified nano-silicon carbide parts can be 90 parts, 92 parts, 94 parts, 95 parts, 96 parts or 98 parts. Further, the number of modified nano-silicon carbide parts can be a range value formed between any two of the above-mentioned point values. Further, the number of modified nano-silicon carbide parts is 96 to 98 parts.

[0048] The above “0.5 to 7.0 parts of sintering aid” can be understood as the number of sintering aids can be 0.5, 1, 2, 3, 4, 5, 6 or 7. Further, the number of sintering aids can be a range value between any two of the above points. Further, the number of sintering aids is 1 to 2.5 parts.

[0049] The above “0.5 to 3.0 parts of toner” can be understood as the number of toners can be 0.5, 1, 1.5, 2, 2.5 or 3. Further, the number of toners can be a range value between any two of the above point values. Further, the number of toners is 0.8 to 1.5.

[0050] Furthermore, the total weight of the modified nano silicon carbide, sintering aid and carbon powder is 100 parts.

[0051] In some embodiments, the silicon carbide ceramic comprises 90wt% to 98wt% of nano silicon carbide, 0.5wt% to 5.0wt% of sintering aid, and 0.5wt% to 3.0wt% of carbon powder, by weight percentage. Further, the silicon carbide comprises 96wt% to 98wt% of nano silicon carbide, 1wt% to 2.5wt% of sintering aid, and 0.8wt% to 1.5wt% of carbon powder.

[0052] In some embodiments, in the nano-α-silicon carbide with a polymer resin layer coated on the surface, the thickness of the polymer resin layer is 5nm~10nm. It can be understood that in the nano-α-silicon carbide with a polymer resin layer coated on the surface, the thickness of the polymer resin layer can be 5nm, 6nm, 7nm, 8nm, 9nm or 10nm. Further, in the nano-α-silicon carbide with a polymer resin layer coated on the surface, the thickness of the polymer resin layer can be a range value consisting of any two point values ​​mentioned above. Preferably, in the nano-α-silicon carbide with a polymer resin layer coated on the surface, the thickness of the polymer resin layer is 6nm~8nm. Controlling the thickness of the polymer resin layer is conducive to further improving the dispersion uniformity of nano-α-silicon carbide, improving the uniformity of the silicon carbide embryo, and then improving the sintering uniformity of silicon carbide ceramics; at the same time, it can further control the densification rate of ceramic grains and improve the density and uniformity of ceramics.

[0053] In some embodiments, the mass of the polymer resin layer is 2wt% to 5wt% of the mass of the nano-α-silicon carbide. By controlling the amount of the polymer resin layer, the rapid densification of the ceramic grains can be further improved to avoid abnormal grain growth.

[0054] In some embodiments, the average particle size of nano-α-silicon carbide is 20nm~200nm. It is understood that the average particle size of nano-α-silicon carbide is 20nm, 40nm, 50nm, 60nm, 80nm, 100nm, 120nm, 150nm, 160nm, 180nm or 200nm. Further, the average particle size of nano-α-silicon carbide is a range value that can be composed of any two of the above point values. Preferably, the average particle size of nano-α-silicon carbide is 50nm~120nm. By controlling the average particle size of nano-α-silicon carbide, the ceramic particle size uniformity can be better, it is not easy to agglomerate, and the particle size distribution is uniform.

[0055] In some embodiments, the material of the polymer resin layer is epoxy resin.

[0056] In some embodiments, the epoxy resin is selected from at least one of bisphenol A epoxy resin, diglycidyl ether, hydantoin epoxy resin, phenolic resin, and polyester resin. Preferably, the epoxy resin is hydantoin epoxy resin and phenolic resin.

[0057] In some embodiments, the sintering aid is selected from at least one of aluminum oxide, yttrium oxide, magnesium oxide, boron, boron carbide, boron phosphide, boron nitride, aluminum nitride and aluminum. Preferably, the sintering aid is selected from at least one of aluminum oxide, yttrium oxide and magnesium oxide.

[0058] In some embodiments, the average particle size of the sintering aid is 50nm~500nm. It is understood that the average particle size of the sintering aid is 50nm, 100nm, 200nm, 300nm, 400nm or 500nm, 700nm or 800nm. Further, the average particle size of the sintering aid can be a range value consisting of any two of the above point values. Preferably, the average particle size of the sintering aid is 50nm~200nm.

[0059] In some embodiments, the average particle size of the carbon powder is 20nm to 200nm. It is understood that the average particle size of the carbon powder is 20nm, 30nm, 50nm, 60nm, 80nm, 100nm, 150nm or 200nm. Further, the average particle size of the carbon powder can be a range value consisting of any two of the above point values. Preferably, the average particle size of the carbon powder is 60nm to 100nm.

[0060] In some embodiments, the nano-α-silicon carbide is surface-hydroxylated nano-α-silicon carbide.

[0061] In some embodiments, the modified nano-silicon carbide further comprises a non-ionic surfactant, which is connected to the surface of the polymer resin layer. Connecting the non-ionic surfactant to the surface of the polymer resin layer can further improve the dispersibility between the modified nano-silicon carbide, thereby improving the uniformity of the grain structure of the silicon carbide ceramic.

[0062] In some embodiments, the nonionic surfactant is selected from at least one of dipropylene triamine (TCI) and coconut fatty acid diethylamide. Preferably, the nonionic surfactant is dipropylene triamine (TCI).

[0063] In some embodiments, the raw materials for preparation further include 1 to 3 parts of a binder by weight. Adding a binder component is beneficial to the molding of the raw material powder during the preparation process.

[0064] In some embodiments, the adhesive is selected from at least one of paraffin, polyethylene glycol, polyvinyl alcohol, and rubber.

[0065] In some embodiments, the mass of the adhesive is 1wt% to 3wt% of the total mass of the modified nano-silicon carbide, modified nano-silicon carbide, sintering aid and carbon powder. Further, the mass of the adhesive is 1.5wt% to 2wt% of the total mass of the modified nano-silicon carbide, modified nano-silicon carbide, sintering aid and carbon powder.

[0066] In one embodiment, a method for preparing the silicon carbide ceramic is provided, comprising the following preparation steps S10 to S20.

[0067] S10, mixing the above-prepared raw materials, and then forming them to obtain a ceramic body.

[0068] S20, sequentially performing degreasing treatment and sintering treatment on the ceramic body.

[0069] In some embodiments, the temperature of the degreasing treatment is 350° C. to 500° C. It is understood that the temperature of the degreasing treatment may be 350° C., 400° C., 450° C. or 500° C. Further, the temperature of the degreasing treatment may be a range value consisting of any two of the above point values.

[0070] In some embodiments, the degreasing treatment time is 1 hour to 3 hours.

[0071] In some embodiments, the temperature of the sintering treatment is 1850°C to 2150°C. It is understood that the temperature of the sintering treatment can be 1850°C, 1900°C, 1950°C, 2000°C, 2050°C, 2100°C or 2150°C. Further, the temperature of the degreasing treatment can be a range value consisting of any two of the above point values. Preferably, the sintering temperature is 1900°C to 2000°C.

[0072] In some embodiments, the sintering time is 2 hours to 4 hours.

[0073] In some embodiments, the degreasing and sintering of the ceramic body can be carried out in a sintering furnace, and the temperature rising program of the sintering furnace is to increase the temperature to 350°C~500°C at a rate of 1°C / min~3°C / min, and keep it warm for 1h~3h; then increase the temperature to 1850°C~2150°C at a rate of 2°C / min~10°C / min, and keep it warm for 2h~4h.

[0074] In some embodiments, the degreasing process and the sintering process can be performed under protective gas conditions. In some embodiments, the protective gas is at least one of hydrogen and nitrogen.

[0075] In some embodiments, the forming step is performed by cold pressing. As an example, the forming step can be performed by cold isostatic pressing.

[0076] In some embodiments, the molding pressure is 50MPa to 300MPa. It is understood that the molding pressure can be 50MPa, 100MPa, 150MPa, 200MPa, 250MPa or 300MPa. Further, the molding pressure can be a range value consisting of any two of the above point values. Preferably, the molding pressure is 150MPa to 200MPa.

[0077] In some embodiments, the holding time in the molding step is 30s to 100s.

[0078] In some embodiments, the step of granulating the mixture is further included before the molding step, and a composite powder having an average particle size of 50 μm to 200 μm is obtained by the granulation step. The composite powder having a specific particle size obtained by granulation is conducive to a more uniform distribution of the nano-silicon carbide powder in the ceramic body, which is more conducive to sintering uniformity, and obtaining silicon carbide ceramics with uniform grains.

[0079] In some embodiments, the granulation can be performed by spray granulation, dry pressing granulation or cold isostatic pressing granulation. Preferably, the granulation is performed by spray granulation.

[0080] In some embodiments, the spray drying temperature in the spray granulation is 80°C to 120°C.

[0081] In some embodiments, after the raw materials are mixed and before the granulation step, a step of ball milling the mixed materials is also included.

[0082] In some embodiments, the ball milling is performed by wet ball milling.

[0083] In some embodiments, the dispersion medium for ball milling is anhydrous ethanol or deionized water.

[0084] In some embodiments, the ball milling medium is selected from at least one of silicon carbide balls, zirconium oxide balls, agate balls, quartz balls, stainless steel balls, and corundum balls.

[0085] In some embodiments, the ball-to-material ratio of ball milling is (1-5):1. The ball-to-material ratio refers to the ratio of the mass of the ball milling medium to the total mass of the prepared raw materials. Further, the ball-to-material ratio is (2-3):1.

[0086] In some embodiments, the ball milling time is 12 h to 48 h. Further, the ball milling time is 24 h to 36 h.

[0087] In some embodiments, the ball milling speed is 50 r / min to 500 r / min. Further, the ball milling speed is 80 r / min to 160 r / min.

[0088] In some embodiments, the above preparation method further includes a preparation step of modified nano-silicon carbide, and the preparation step of modified nano-silicon carbide includes the following steps S11 to S12.

[0089] S11, subjecting the nano-α-silicon carbide to hydroxylation to obtain surface hydroxylated nano-α-silicon carbide.

[0090] S12, coating the surface of the hydroxylated silicon carbide with a polymer resin to obtain nano-α-silicon carbide having a surface coated with a polymer resin layer.

[0091] In some embodiments, the hydroxylation treatment of nano-α-silicon carbide includes the following steps S111 to S113.

[0092] S111, pouring nano-α-silicon carbide into a hydrogen peroxide solution, performing dispersion treatment, and obtaining a first mixed material.

[0093] S112, reflux the first mixture at 100° C. to 120° C. for 4 h to 12 h; then perform solid-liquid separation, collect and wash solid particles to obtain surface hydroxylated nano-α-silicon carbide.

[0094] In some embodiments, the dispersion method in the above step S111 can be dispersion by stirring or ultrasonic treatment.

[0095] In some embodiments, the dispersion treatment time is 10 min to 60 min.

[0096] In some embodiments, the solid-liquid separation may be performed by centrifugal sedimentation.

[0097] In some embodiments, the centrifugal sedimentation time is 5 min to 30 min.

[0098] In some embodiments, the concentration of hydrogen peroxide in the hydrogen peroxide solution is 15 wt % to 40 wt %.

[0099] In some embodiments, the method of coating the surface of the hydroxylated silicon carbide with a polymer resin in the above step S112 comprises the following steps:

[0100] pouring the surface hydroxylated nano-α-silicon carbide into a polymer resin solution to obtain a suspension;

[0101] A pH adjuster was added to adjust the pH value of the suspension to 1-3, and the first reaction was carried out.

[0102] In some embodiments, the concentration of the polymer resin in the polymer resin solution is 5 wt % to 10 wt %.

[0103] In some embodiments, the pH adjuster is selected from at least one of dilute hydrochloric acid and dilute sulfuric acid.

[0104] In some embodiments, the temperature of the first reaction is 40°C to 80°C.

[0105] In some embodiments, the first reaction time is 2 h to 4 h.

[0106] In some embodiments, the preparation step of modified nano-silicon carbide further includes the following step S13.

[0107] S13, connecting a nonionic surfactant to the surface of the nano-α-silicon carbide coated with a polymer resin layer.

[0108] In some embodiments, a method for connecting a nonionic surfactant to the surface of nano-α-silicon carbide coated with a polymer resin layer comprises the following steps:

[0109] After the first reaction in the above step S112 is completed, a nonionic surfactant is added, and the mixture is stirred at room temperature for 8 h to 24 h, and then stirred at 60° C. to 100° C. for 1 h to 4 h.

[0110] In some embodiments, after the step of connecting a non-ionic surfactant to the surface of the nano-α-silicon carbide coated with a polymer resin layer, the steps of solid-liquid separation, washing and drying are also included.

[0111] In some embodiments, the above-mentioned cleaning may use deionized water to clean the solid particles.

[0112] In some embodiments, the drying condition may be vacuum drying at 40° C. to 80° C.

[0113] In some embodiments, the drying time is 8 hours to 24 hours.

[0114] In order to make the purpose, technical solutions and advantages of the present invention more concise and clear, the present invention is described with the following specific embodiments, but the present invention is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present invention, which can be used to describe the present invention and cannot be understood as limiting the scope of the present invention. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0115] In order to better illustrate the present invention, the present invention is further described below in conjunction with the embodiments. The following are specific embodiments.

[0116] Example 1

[0117] Nano-SiC surface modification:

[0118] (1) α-SiC nanoparticles with an average particle size of 80 nm were poured into a 30 wt% H2O2 aqueous solution and ultrasonically dispersed for 30 min, then heated to 106 °C and refluxed for 6 h. The SiC nanoparticles were then collected by centrifugal sedimentation for 15 min and washed with deionized water to obtain surface hydroxylated α-SiC nanoparticles.

[0119] (2) The surface hydroxylated α-silicon carbide nanoparticles obtained in step (1) are poured into a 10 wt% aqueous solution of hydantoin epoxy resin (product model: MHR-070) so that the mass of hydantoin epoxy resin is 3 wt% of the total mass of the nano-silicon carbide powder. Dilute sulfuric acid is then added to make the pH value of the mixed solution 1.0. The mixture is then stirred at 60° C. for 2 h to obtain a suspension of α-silicon carbide nanoparticles coated with an epoxy resin layer.

[0120] (3) Add 3 wt% of dipropylene triamine (TCI) to the suspension in step (2), and stir at room temperature for 16 h, and then stir at 60 ° C for 2 h. Then centrifuge and collect the silicon carbide nanoparticles, wash the nano silicon carbide with deionized water, and vacuum dry at 80 ° C for 12 h to obtain the modified silicon carbide nanopowder.

[0121] Figure 1 This is a microscopic morphology of the nano-silicon carbide powder modified with hyaluronic acid resin obtained in step (3) of Example 1. Figure 1 It can be seen that the surface of nano-silicon carbide is evenly coated with hyaluronic acid epoxy resin, with uniform thickness and complete structure.

[0122] Preparation method of ultrafine grain silicon carbide ceramics:

[0123] (1) Weigh the raw materials according to the formula and set aside. The specific formula is: 97.7 parts of modified nano silicon carbide powder, 1.5 parts of boron carbide powder, 0.8 parts of pyrolytic carbon black powder, and 2 parts of polyethylene glycol. The nano silicon carbide is α-silicon carbide with an average particle size of 80 nm, the average particle size of the boron carbide powder is 200 nm, and the average particle size of the pyrolytic carbon black powder is 50 nm.

[0124] (2) The modified nano silicon carbide powder is mixed with a sintering aid and carbon powder, and polyethylene glycol is added thereto; wet ball milling is then performed, wherein the ball milling time is 24 hours, the ball milling medium is anhydrous ethanol, the ball-to-material ratio is 2:1, and the rotation speed is 120 r / min to obtain a mixed slurry.

[0125] (3) The mixed slurry is spray granulated to obtain spherical composite powder with a particle size of 150 μm.

[0126] (4) The composite powder is then subjected to cold isostatic pressing to obtain a nano-silicon carbide ceramic blank. The molding pressure is 200 MPa and the holding time is 60 s.

[0127] (5) The formed nano-SiC ceramic blank is first heated to 400°C at a rate of 2°C / min and kept at that temperature for 2 hours under vacuum conditions for degreasing treatment, and then heated to 1980°C at a rate of 5°C / min and kept at that temperature for 3 hours for high-temperature sintering treatment. It is then cooled to room temperature in the furnace to obtain ultrafine-grained SiC ceramics.

[0128] Example 2

[0129] Nano-SiC surface modification:

[0130] (1) α-SiC nanoparticles with a particle size of 60 nm were poured into a 20 wt% H2O2 aqueous solution and ultrasonically dispersed for 30 min, then heated to 105 °C and refluxed for 8 h. The nano-SiC particles were collected by centrifugal sedimentation for 20 min and washed with deionized water to obtain surface hydroxylated α-SiC nanoparticles.

[0131] (2) Pour 8.0wt% aqueous solution of hydantoin epoxy resin (product model: MHR-070) into the surface hydroxylated α-silicon carbide nanoparticles obtained in step (1), wherein the amount of hydantoin in the epoxy resin is 4.0wt% of the mass of the nano-silicon carbide powder, and then add dilute sulfuric acid to make the pH value of the mixed solution 1.5, and then stir at 60°C for 2h to obtain a suspension of α-silicon carbide nanoparticles with a surface coated with an epoxy resin layer.

[0132] (3) Add 4 wt% of dipropylenetriamine (TCI) to the mixed suspension of step (2), and stir at room temperature for 20 h, and then stir at 60 ° C for 2 h; then centrifuge and collect the silicon carbide nanoparticles, wash the nano silicon carbide powder with deionized water, and vacuum dry at 60 ° C for 12 h to obtain the modified silicon carbide nanopowder.

[0133] The surface of the modified nano-silicon carbide is uniformly coated with epoxy resin, with uniform thickness and complete structure.

[0134] Preparation method of ultrafine grain silicon carbide ceramics:

[0135] (1) Weigh the raw materials according to the formula and set aside. The specific formula is: 96.0 parts of modified nano silicon carbide (SiC) powder, 0.8 parts of boron powder, 2.0 parts of aluminum nitride powder, 1.2 parts of pyrolytic carbon black, and 2 parts of polyethylene glycol, wherein the average particle size of the boron powder is 80 nm, the average particle size of the aluminum nitride is 100 nm, and the average particle size of the pyrolytic carbon black powder is 80 nm.

[0136] (2) The modified nano silicon carbide powder is mixed with a sintering aid and carbon powder, and polyethylene glycol is added thereto; wet ball milling is then performed, wherein the ball milling time is 24 hours, the ball milling medium is anhydrous ethanol, the ball-to-material ratio is 3:1, and the rotation speed is 100 r / min to obtain a mixed slurry.

[0137] (3) The mixed slurry is spray granulated to obtain spherical composite powder with a particle size of 100 μm.

[0138] (4) The composite powder is then subjected to cold isostatic pressing to obtain a nano-silicon carbide ceramic blank. The molding pressure is 150 MPa and the holding time is 80 s.

[0139] (5) The formed nano-SiC ceramic blank is first heated to 450°C at a rate of 2°C / min and kept at that temperature for 3 hours under vacuum conditions for degreasing treatment, and then heated to 1950°C at a rate of 6°C / min and kept at that temperature for 2 hours for high-temperature sintering treatment. It is then cooled to room temperature in the furnace to obtain ultrafine-grained SiC ceramics.

[0140] Example 3

[0141] Nano-SiC surface modification:

[0142] (1) Pour α-SiC nanoparticles with a particle size of 80 nm into a 40 wt% H2O2 aqueous solution, stir or ultrasonically disperse for 30 min, then heat to 120 °C and reflux for 4 h. Then collect the SiC nanoparticles by centrifugal sedimentation for 10 min and wash with deionized water to obtain surface hydroxylated α-SiC nanoparticles.

[0143] (2) The surface hydroxylated α-silicon carbide nanoparticles obtained in step (1) are poured into a 5.0 wt% aqueous solution of hydantoin epoxy resin (product model: MHR-070), wherein the amount of hydantoin epoxy resin is 1.0 wt% of the mass of the nano-silicon carbide powder, and then dilute sulfuric acid is added to make the pH value of the mixed solution 2, and then stirred at 60°C for 1 hour to obtain a suspension of α-silicon carbide nanoparticles with a surface coated with an epoxy resin layer.

[0144] (3) Add 2 wt% of dipropylene triamine (TCI) to the suspension of step (2), and stir at room temperature for 12 h, and then stir at 60 ° C for 1 h. Then centrifuge to collect silicon carbide nanoparticles, wash the nano silicon carbide powder with deionized water, and vacuum dry at 80 ° C for 24 h to obtain the modified silicon carbide nanopowder.

[0145] The surface of the modified nano-silicon carbide is uniformly coated with epoxy resin, with uniform thickness and complete structure.

[0146] Preparation method of ultrafine grain silicon carbide ceramics:

[0147] (1) Weigh the raw materials according to the formula and set aside. The specific formula is: 92.0 parts of modified nano silicon carbide powder, 3.5 parts of aluminum nitride powder, 3.5 parts of yttrium oxide powder, 1.0 part of pyrolytic carbon black, and 3 parts of polyethylene glycol, wherein the average particle size of the aluminum nitride powder is 100 nm, the average particle size of the yttrium oxide powder is 120 nm, and the average particle size of the pyrolytic carbon black powder is 80 nm.

[0148] (2) The modified nano silicon carbide powder is mixed with a sintering aid and carbon powder, and polyethylene glycol is added thereto; wet ball milling is then performed, wherein the ball milling time is 12 h, the ball milling medium is anhydrous ethanol, the ball-to-material ratio is 1:1, and the rotation speed is 120 r / min to obtain a mixed slurry.

[0149] (3) The mixed slurry is spray granulated to obtain spherical composite powder with a particle size of 200 μm.

[0150] (4) The composite powder is then subjected to cold isostatic pressing to obtain a nano-silicon carbide ceramic blank. The molding pressure is 200 MPa and the holding time is 30 s.

[0151] (5) The formed nano-SiC ceramic blank is first heated to 500°C at a rate of 3°C / min and kept at this temperature for 2 hours under vacuum conditions for degreasing treatment, and then heated to 2000°C at a rate of 5°C / min and kept at this temperature for 2 hours for high-temperature sintering treatment. It is then cooled to room temperature in the furnace to obtain ultrafine-grained SiC ceramics.

[0152] Example 4

[0153] The preparation method of this embodiment is basically the same as that of embodiment 2, except that step (1) is omitted when surface modification of nano-silicon carbide is performed in this embodiment, and the nano-silicon carbide particles are directly poured into an aqueous solution of 8.0 wt % hydantoin epoxy resin, wherein the hydantoin epoxy resin accounts for 4.0 wt % of the total mass of the powder. Other process conditions and parameters are the same as those of embodiment 2.

[0154] The surface of the modified nano-silicon carbide obtained in this example is partially coated with epoxy resin, and its thickness uniformity and structural integrity are not as good as those in Example 2. The uniformity of the grain structure of the obtained ultrafine-grained silicon carbide ceramic is also not as good as that in Example 2.

[0155] Example 5

[0156] The preparation method of this embodiment is basically the same as that of embodiment 3, except that the sintering temperature in step (5) of the preparation step of ultrafine grained silicon carbide ceramics is set to 2200° C. Other process conditions and parameters are the same as those of embodiment 3.

[0157] Example 6

[0158] The preparation method of this embodiment is basically the same as that of Example 1, with the only difference being that in this embodiment, 1.5 parts of boron carbide powder in Example 1 is replaced with 1.5 parts of aluminum oxide in the preparation method of ultrafine-grained silicon carbide ceramics, and other process conditions and parameters are the same as those in Example 1.

[0159] Example 7

[0160] The preparation method of this embodiment is consistent with that of embodiment 1, except that step (3) is omitted in the preparation of modified nano-α-silicon carbide in this embodiment, that is, the surface of the modified tantalum carbide in this embodiment is not connected with a non-ionic surfactant. Other process conditions and parameters are consistent with those of embodiment 1.

[0161] Example 8

[0162] The preparation method of this embodiment is consistent with that of embodiment 1, and the only difference is that the polymer resin solution used in step (2) of this embodiment is different when preparing modified nano-silicon carbide. Specifically, step (2) of this embodiment is: pouring the surface hydroxylated α-silicon carbide nanoparticles obtained in step (1) into a 10wt% aqueous solution of bisphenol A epoxy resin (product model: EP01441-310) so that the mass of bisphenol A epoxy resin is 3wt% of the total mass of nano-silicon carbide powder, and then adding dilute sulfuric acid so that the pH value of the mixed solution is 1.0, and then stirring at 60°C for 2h to obtain a suspension of α-silicon carbide nanoparticles with an epoxy resin layer on the surface. Other process conditions and parameters are consistent with those of embodiment 1.

[0163] Example 9

[0164] The preparation method of this embodiment is consistent with that of embodiment 1, and the only difference is that the polymer resin solution used in step (2) of this embodiment is different when preparing modified nano-silicon carbide. Specifically, step (2) of this embodiment is: pouring the surface hydroxylated α-silicon carbide nanoparticles obtained in step (1) into a 10wt% aqueous solution of phenolic resin (product model: CAS: 9003-35-4) so ​​that the mass of bisphenol A type epoxy resin is 3wt% of the total mass of nano-silicon carbide powder, and then adding dilute sulfuric acid so that the pH value of the mixed solution is 1.0, and then stirring at 60°C for 2h to obtain a suspension of α-silicon carbide nanoparticles with an epoxy resin layer on the surface. Other process conditions and parameters are consistent with those of embodiment 1.

[0165] Comparative Example 1

[0166] The preparation methods of this comparative example are basically the same as those of Example 1, with the only difference being that in the preparation method of the ultrafine-grained silicon carbide ceramic in this comparative example, the modified nano-α-silicon carbide in Example 1 is replaced with an equal amount of unmodified nano-α-silicon carbide, that is, the α-silicon carbide nanoparticle raw material in step (1) is directly used, and the nano-α-silicon carbide in this comparative example has not been surface-modified. Other process conditions and parameters are the same as those in Example 1.

[0167] Comparative Example 2

[0168] The preparation method of this comparative example is basically the same as that of Example 1, with the only difference being that in this comparative example, β-silicon carbide is used in the silicon carbide surface modification step, and other modification conditions and parameters are consistent with those of Example 1; an equal amount of modified β-silicon carbide is used in the step of preparing silicon carbide ceramics, and other preparation process conditions and parameters are consistent with those of Example 1.

[0169] Performance Testing Methods

[0170] Average grain size of silicon carbide ceramics: Samples are taken at 5 different locations of the ceramics, and the grain sizes at different locations are tested according to the method specified by the intercept method, and the average value is taken. The intercept method test steps are as follows: 1) Draw a straight line with a length of 25μm on the scanning electron microscope photo (5000×), 2) Calculate the number of intercepts of the intersection of the test line segment (or grid) of known length and the grain interface; 3) Use the number of intercepts per unit length to determine the grain size grade.

[0171] Vickers hardness: Tested according to the method specified in GB / T 16534-2009.

[0172] Bending strength: Tested in accordance with the method specified in GB / T 4741-1999.

[0173] Thermal conductivity: Tested in accordance with the method specified in GB T 39862-2021.

[0174] Relative density: Test according to the method specified by Archimedes drainage method. The test steps of Archimedes drainage method are as follows: 1) Measure the weight of ceramics in air; 2) Pour water into the overflow cup, immerse the ceramic block in the overflow cup, and read the weight of the ceramics in water; 3) Calculate the total gravity of the displaced water; 4) Calculate the relative density of the ceramics.

[0175] The performance test data of each embodiment and comparative example are shown in Table 1:

[0176] Table 1

[0177]

[0178] From Table 1, it can be seen that the silicon carbide ceramics prepared in Examples 1-9 have a small average grain size, high Vickers hardness and flexural strength, and high thermal conductivity and relative density. Figure 2 is the SEM image of the silicon carbide ceramic in Example 1. Figure 2 It can be seen that the silicon carbide ceramic obtained in Example 1 is an ultrafine-grained silicon carbide ceramic with uniform structure and high density. It can be seen that an ultrafine-grained silicon carbide ceramic with high thermal conductivity and good mechanical properties can be obtained through the technical solution of the present application.

[0179] Comparative Example 1 Compared with Example 1, in Comparative Example 1, the surface of nano-silicon carbide was not modified when preparing silicon carbide ceramics. Figure 3 It can be seen that the silicon carbide ceramic obtained in Comparative Example 1 is a coarse-grained silicon carbide ceramic, whose grain size is relatively uneven and has abnormally grown grains. Combined with Table 1, the average grain size of the silicon carbide ceramic obtained in Comparative Example 1 is larger, and the bending strength, thermal conductivity and relative density are not as good as those in Example 1.

[0180] Compared with Example 2, Comparative Example 2 is different in that the nano silicon carbide used in Comparative Example 2 is β-silicon carbide, and the silicon carbide ceramic obtained in Comparative Example 2 is a coarse-grained silicon carbide ceramic, which has a relatively uniform structure, but a relatively low density; combined with Table 1, it can be seen that the silicon carbide ceramic of Comparative Example 2 has a large average grain, and its bending strength and thermal conductivity are not as good as those of Example 2. This is because the raw material powder of Comparative Example 2 is β-silicon carbide, which will be converted into α-SiC when heated at high temperature, promoting crystal transformation, causing abnormal grain growth, and thus causing its silicon carbide ceramic performance to be inferior to that of Example 2.

[0181] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0182] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A silicon carbide ceramic, characterized in that: The raw materials for its preparation include modified nano silicon carbide, sintering aid and carbon powder; the modified nano silicon carbide includes nano α-silicon carbide, a polymer resin layer and a non-ionic surfactant, the polymer resin layer is coated on the surface of the nano α-silicon carbide; the non-ionic surfactant is connected to the surface of the polymer resin layer; The nano-α-silicon carbide is surface hydroxylated nano-α-silicon carbide; The material of the polymer resin layer is selected from at least one of bisphenol A epoxy resin, hydantoin epoxy resin and phenolic resin; The nonionic surfactant is selected from at least one of dipropylene triamine and coconut fatty acid diethylamide.

2. The silicon carbide ceramic according to claim 1, characterized in that Calculated by weight, the raw materials include 90 to 98 parts of modified nano silicon carbide, 0.5 to 7.0 parts of sintering aids and 0.5 to 3.0 parts of carbon powder.

3. The silicon carbide ceramic according to claim 1, characterized in that The silicon carbide ceramic meets at least one of the following conditions: (1) In the modified nano-silicon carbide, the thickness of the polymer resin layer is 5 nm to 10 nm; (2) The average particle size of the nano-α-silicon carbide is 20nm to 200nm; (3) The mass of the polymer resin layer is 2wt% to 5wt% of the mass of the nano-α-silicon carbide.

4. The silicon carbide ceramic according to claim 1, characterized in that The silicon carbide ceramic meets at least one of the following conditions: (1) The sintering aid is at least one selected from alumina, yttrium oxide, magnesium oxide, boron, boron carbide, boron phosphide, boron nitride, aluminum nitride and aluminum; (2) The average particle size of the sintering aid is 50nm to 500nm; (3) The average particle size of the carbon powder is 20nm to 200nm.

5. The silicon carbide ceramic according to any one of claims 1 to 4, characterized in that: The raw materials for preparation further include 1 to 3 parts of a binder in terms of mass.

6. The method for preparing silicon carbide ceramics according to any one of claims 1 to 5, characterized in that: The steps include: The prepared raw materials are mixed and then molded to obtain a ceramic body; The ceramic body is subjected to degreasing treatment and sintering treatment in sequence.

7. The preparation method according to claim 6, characterized in that: The degreasing treatment is performed at a temperature of 350° C. to 500° C. for a time of 1 h to 3 h; and / or the sintering treatment is performed at a temperature of 1850° C. to 2150° C. for a heat preservation time of 2 h to 4 h.

8. The preparation method according to claim 6, characterized in that: The preparation method also includes a preparation step of modified nano-silicon carbide, including: The nano-α-silicon carbide is subjected to hydroxylation treatment to obtain surface hydroxylated nano-α-silicon carbide; The surface of the hydroxylated nano-α-silicon carbide is coated with a polymer resin to obtain the nano-α-silicon carbide with a polymer resin layer coated on the surface.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The preparation steps of the modified nano-silicon carbide also include: The step of connecting a nonionic surfactant to the surface of the nano-α-silicon carbide coated with a polymer resin layer.

10. The preparation method according to any one of claims 6 to 8, characterized in that: The preparation method further comprises a granulation step before the molding step, and obtains a composite powder with an average particle size of 50 μm to 200 μm.

11. The preparation method according to any one of claims 6 to 8, characterized in that: The molding is performed by cold pressing, and the molding pressure is 50MPa to 300MPa.